Structural Modeling on PSiOS - Patel, Jay (My University, 2016)
In this thesis, an integrated system model is germinated for the structure of the privacy and security of iOS (PSiOS) devices with the help of the Matrix Algebra and Graph Theory to compare the Graphs. Firstly, the structure of the PSiOS is sculptural using Graph Theory, secondly using Variable Adjacency Matrix and last by a polynomial which is known as Permanent Function. In terms of Storage Optimization and execution time of a program, the Permanent Function provides a chance to effectuate the structural Analysis of PSiOS by comparing the properties of PSiOS with it. To germinate the Graph Model, Matrix Model and a polynomial permanent model, antithetic structural attributes of the PSiOS are identified. For the complete analysis of PSiOS system, top-down approach is also exemplified.
Keywords: Structural Modeling, PSiOS